Mengelola Corporate Crisis Melalui Transformasi Model Stakeholder Relations di Era Digital - Helpris Estaswara; Diana Anggraeni (CoverAge: Journal of Strategic Communication, 2018)
Managing stakeholders in the era of digital society become more complicated and the corporate crisis is highly potential to come forward. Consequently, to develop a long-term profitable relationship with the stakeholders requires dialogue based method. However, many corporate implement stakeholder relationship model remain derived from the understanding that corporate is the centre of all stakeholders, or corporate-centric model. A new model of system-centric than proposed in order to deal with the stakeholders in the era of digital society. The model implies that the corporate will be no longer being a central of stakeholders. It means the position of the corporate being a part of the system and involve symmetrical two-way communication strategy. This paper aimed at, firstly to elaborate a social network that would be potential to create the crisis if the corporate is not implementing the system-centric model that requires the development of multi-stakeholders learning dialogues. Secondly, it also analyzed the steps should be taken into account in order to transform traditional model toward symmetrical communication model of stakeholder relationship. Furthermore, method of literature review was applied as a basis of theoretical construction on stakeholder relationship model that should be engaged in avoiding of the crisis.